Influence of E-Recruitment and Job Characteristic on Pursuit Job Intention with Company Reputation as Moderator - Nabila Gina; Yuni Siswanti; Sudaryati Sudaryati (Journal of International Conference Proceedings, 2024)
This study aims to determine the influence of e-recruitment and job characteristics on the pursuit of job intention of graduated student University in Yogyakarta city and company reputation as moderating variable. The study uses multiple linear regression analysis and moderated regression analysis with SPSS (Statistical Package for the Social Sciences) as a test tool. Sampling was carried out using purposive sampling, and the number of samples was 87 graduated students from 2017 2018 at ABC University, especially in the Management Study Program. The result of this research indicates that e-recruitment and job characteristics have a positive effect and significance on job pursuit intention. Company reputation as a moderate variable can strengthen the relationship between e-recruitment and interest in applying for work and job characteristics with interest in applying for work. The novelty of this research is that the company's reputation is one of the important variables that can strengthen the influence of recruitment and job characteristics on the interest of job seekers, where the results of previous research are still minimal. This research has theoretical and practical implications that are important to discuss further